Knowledge Description of S1 Nursing Study Program Students Semester II STIKes Santa Elisabeth Medan about BSE in the Santa Agnes Girls Dormitory 2022: 2017-2021 - Meriati Bunga Arta Purba; Magda Siringo-ringo; Riska Debora Pardede (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
To detect breast cancer early, the effort that women can do by means of Breast Self-Examination or BSE. BSE is an increase in a woman's interest in the state of her own breasts. Women's knowledge still minimal about accurate information on breast cancer and early detection efforts. Understanding of breast cancer and early detection efforts still need to be improved so that the chances of recovery and the number of life ambitions increase. So that the morbidity and mortality of breast cancer sufferers reduced and the quality of life of breast cancer patients is increased. To describe the knowledge of S1 Nursing Study Program Students Semester II STIKes Santa Elisabeth Medan about BSE the Santa Agnes Girls Dormitory in 2022. This type of research is descriptive with a total sampling technique with data collection techniques carried out using a questionnaire distributed via google form. The results of 80 respondents who had sufficient knowledge were 63 respondents (79%) and 17 respondents (21%). Students are expected to increase their knowledge about BSE by digging more information about BSE, through the internet or other mass media. Thus, students more confident in implementing and carrying out breast self-examination measures within themselves, so that breast cancer detected as early as possible and the number of breast cancer sufferers decrease.